EFFECTS OF CATION DISTRIBUTION ON THE MAGNETIC AND ELECTRICAL-PROPERTIES OF COBALT FERRITE - NA, JG; LEE, TD; PARK, SJ (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 1992)
The effects of cation distribution on the magnetic and electrical properties of cobalt ferrites are investigated. To this end, variation of the saturation magnetization, the electrical resistivity, the Hall parameters and the Seebeck coefficient with quenching temperature was measured in cobalt ferrites, CoxFe3-xO4 (X = 0.94, 0.97, 1.00 and 1.03). With increasing quenching temperature, the saturation magnetization of cobalt ferrites increases and the electrical resistivity decreases. The Hall measurements indicate that the decrease in the electrical resistivity in cobalt ferrites is attributed to increase of the electron concentration. The conducting mechanism of cobalt ferrites except for Co1.03Fe1.97O4 is identified to be n-type. For Co1.03Fe1.97O4, however, conducting mechanism changes from p-type (for the furnace-cooled specimen) to n-type (for the specimens of gas-quenched at 900 and 1200-degrees-C). The changes in the Ms, electron concentration and the Seebeck coefficient of cobalt ferrites by quenching heat treatment are related to the Fe ion migration from tetrahedral sites to octahedral sites and the charge conversion of the Fe ions accompied to site change.